Reinterprestasi Hadis Mesoginik Kepemimpinan Wanita Dalam Musnad Ahmad Perspektif Maqasid Al-Shariah - Wahidul Anam; Mubaidi Sulaeman (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Misogynistic Hadith Reinterpretation of Women's Leadership in Musnad Ahmad Maqasid Al-Shariah PerspectiveThis article aims to reinterpretation the mesoginic hadiths that describe women's leadership in Ahmad's musnad of the maqasid al-shariah perspective. The leadership of Muslim women in the public sphere has indeed experienced a significant development in recent years. But in some Muslim circles, women's leadership in the public sphere is still a taboo and is still clashed with mesoginic hadiths that describe women's leadership. In this study, the method used is a qualitative descriptive method of the library research type. The use of qualitative descriptive methods due to their suitability with the subject matter and focus of the research. The study found: 1) The mesoginic hadith when analyzed using the maqas}id al-shari'ah approach which says that women's leadership in Islam is prohibited, is a partial and textual understanding of hadith. 2) hadith which says women's leadership in Islam is forbidden, in essence indeed in hadith (tahrij hadith) has a continuous continuity of sanad and matan. However, in substance, the hadith requires reinterpretation so that the text and context of the hadith are read and understood wisely by Muslims. The theoretical implication that the author finds is that maqasid al-shari'ah as a science of interpretation, can not only be used to interpret the ahkam verses present in the Qur'an alone, but can also be used to interpret the hadith-hadith ahkam. So the impact is that when Muslims read a hadith they are required to be critical and selective not only in terms of the passage, but also to consider whether the intention of the shari'ah is relevant or not to the context of the times